Contribution of Halal Industry to Economic Growth in Central Tapanuli Regency - Abdullah Hutauruk, Muhammad Zaky; Qarni, Waizul; Silalahi, Purnama Ramadani (Al-Insyiroh: Jurnal Studi Keislaman, 2025)
The purpose of this study is to find out whether there is a contribution of the halal industry to economic growth in Central Tapanuli Regency and how the halal industry contributes to economic growth in Central Tapanuli Regency. The research method used is a qualitative research method. Data collection is carried out by observation, interviews and documentation, with data analysis techniques namely reducing data, presenting data and drawing conclusions. The results of this study show that the halal industry contributes to economic growth in Central Tapanuli from the halal food sector which continues to increase, but due to the size of this district hinders halal industry players from having halal certificates so that only some of them have halal certificates.